2004
DOI: 10.1540/jsmr.40.25
|View full text |Cite
|
Sign up to set email alerts
|

TNF-.ALPHA. augments the expression of RhoA in the rat bronchus

Abstract: While nonspecific airway hyperresponsiveness (AHR) is a central feature of allergic bronchial asthma, the mechanism underlying the developmont of AHR is not clearly understood. We have previously demonstrated in vitro hyperresponsiveness of bronchial smooth muscle to acetylcholine (ACh) in rats that were actively sensitized and repeatedly challenged with aerosolized antigen. It has also been demonstrated that the AChinduced, RhoA-mediated Ca 2+ sensitization is markedly augmented concomitantly with an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
(35 reference statements)
3
22
0
Order By: Relevance
“…4) after application of TNF-α. Consistent with our previous rat study (22), TNF-α caused an upregulation of RhoA in hBSMCs. A significant increase in the level of RhoA mRNA was observed when the cells were stimulated with 10 ng/mL of TNF-α for 6, 12, and 24 h (Fig.…”
Section: Nf-κb Activation By Tnf-α In Hbsmcssupporting
confidence: 93%
See 1 more Smart Citation
“…4) after application of TNF-α. Consistent with our previous rat study (22), TNF-α caused an upregulation of RhoA in hBSMCs. A significant increase in the level of RhoA mRNA was observed when the cells were stimulated with 10 ng/mL of TNF-α for 6, 12, and 24 h (Fig.…”
Section: Nf-κb Activation By Tnf-α In Hbsmcssupporting
confidence: 93%
“…A marked upregulation of RhoA in BSMs has also been demonstrated in these animal models of allergic bronchial asthma (14,15). Although the detailed mechanism(s) of RhoA upregulation is not fully understood, TNF-α might be one of the causes of the phenomenon (8,22).…”
Section: Introductionmentioning
confidence: 91%
“…Additionally, we showed that in cultured human ASM cells TNFα potentiated, also in a non-specific manner, calcium signals in response to different GPCR agonists (Amrani, 2006). Parallel studies further supported the potential role of TNFα-ASM interaction in AHR by showing that TNFα acts by inducing Rho-dependent calcium sensitization (Hunter et al, 2003;Hunter and Nixon, 2006;MacEwan, 2002;McFarlane et al, 2001;Parris et al, 1999;Sakai et al, 2004b). Together, these investigators demonstrate that TNFα promotes AHR by modulating ASM contractility, an effect that could result from an altered GPCR-associated calcium signaling.…”
Section: Introductionmentioning
confidence: 57%
“…TNF-a can activate RhoA/Rho kinase (46), and that inhibition of Rho kinase decreases airway inflammation (47) as well as airway hyperresponsiveness (48,49). Accordingly, it is possible that NT activation of p75NTR can modulate TNF-a effects (and vice versa) on ASM sensitivity for force generation.…”
Section: Tnf-a Nts and The Airwaymentioning
confidence: 99%